2022
DOI: 10.1039/d2ra00134a
|View full text |Cite
|
Sign up to set email alerts
|

Transforming waste into value: pomelo-peel-based nitrogen-doped carbon dots for the highly selective detection of tetracycline

Abstract: We developed an eco-friendly approach utilizing pomelo peel as a carbon source to synthesize P-NCDs, obtaining a high quantum yield of up to 76.47%. Our prepared P-NCDs can recognize tetracycline, and their fluorescence was quenched based on an IFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The average lifetime values of LP-CQDs were 2.09 and 2.03 ns with the addition of TC, showing minimal change in the values of average lifetime (Figure b, Table ), which signifies negligible electron transfer between LP-CQDs and TC; thus, the mechanism was attributed to the IFE. , Furthermore, the mechanism was confirmed by the UV–vis spectra of LP-CQDs, TC, and LP-CQDs + TC. Figure c shows the strengthening of the absorption peak in the presence of TC with no change in peak positions, signifying that no new substance was formed from LP-CQDs and TC Scheme shows the plausible detection mechanism.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The average lifetime values of LP-CQDs were 2.09 and 2.03 ns with the addition of TC, showing minimal change in the values of average lifetime (Figure b, Table ), which signifies negligible electron transfer between LP-CQDs and TC; thus, the mechanism was attributed to the IFE. , Furthermore, the mechanism was confirmed by the UV–vis spectra of LP-CQDs, TC, and LP-CQDs + TC. Figure c shows the strengthening of the absorption peak in the presence of TC with no change in peak positions, signifying that no new substance was formed from LP-CQDs and TC Scheme shows the plausible detection mechanism.…”
Section: Resultsmentioning
confidence: 96%
“…Tetracycline (TC), a broad-spectrum antibiotic with excellent sterilization, disinfection efficiency, antimicrobial activity, and low toxicity, is a cost-effective option. It is extensively utilized in animal husbandry to effectively combat various bacteria that cause diseases including rickettsia, chlamydia, and mycoplasma . However, improper use of TC in veterinary medication along with food products has led to its presence in common food such as milk, meat, and honey .…”
Section: Introductionmentioning
confidence: 99%
“…25 Due to the high repeatability and less by-products, this method is especially suitable for the synthesis of excellent sp 2 structure CDs; whereas, the obtained CDs possess the defects of weak fluorescence performance and low quantum yield. 26 To be specific, the arc discharge was the earliest method to synthesize CDs, but its application is limited by the produced impurities, high energy consumption and low yield. 27 The laser ablation method refers to the use of a high energy laser to irradiate carbon targets in an inert environment, and then reprocess to obtain CDs, however the collected CDs have inferior particle size homogeneity and poor yield.…”
Section: Top-down Strategymentioning
confidence: 99%
“…25 Due to the high repeatability and less by-products, this method is especially suitable for the synthesis of excellent sp 2 structure CDs; whereas, the obtained CDs possess the defects of weak fluorescence performance and low quantum yield. 26…”
Section: Synthesis Of Cdsmentioning
confidence: 99%
“…[4,18,19] Currently, it has been reported that CDs could be used as fluorescence sensors to detect TCs. [20][21][22][23] However, the reported CDs were mainly for the determination of total TC content in samples, and their ability to recognize single TCs (TC, CTC, and OTC) is poor. Therefore, it is very meaningful to develop new CDs to detect TCs.…”
mentioning
confidence: 99%